PENGARUH DISTRIBUSI UKURAN BUTIRAN TERHADAP KOMPLEKSITAS ALIRAN FLUIDA PADA MODEL BATUAN BERPORI 3D - Nur Rahmi; M Najib Alyasyfi; Peny Saptiani; E Riska Rahayu P; Fourier D E Latief; Selly Feranie (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Differences in the distribution of grain size (sorting) in porous rocks can affect the fluid flow complexity even though they have the same porosity. It can be analyzed by performing simple modeling that assumes granules can be represented in perfect overlapping, rounded forms. Rock models can be made by setting the main parameters of the granular radius until the desired porosity is reached. From the model made, the fluid flow complexity can be analyzed by using the tortuosity parameters in the x, y, and z directions of the rock model. Tortuosity is calculated as a comparison between the flow traces passing through the pores connected to the length of the side in the direction of the rock model flow, and trace flow tracking is done by the full random walk cubical method. In measuring the fluid flow complexity in this rock, porosity is made equal to three models, which is 15%. Porous rock models are arranged by placing the grains of varying radius (small, medium, and large) that are randomly distributed and overlapping in a 200 x 200 x 200 medium. From the results of calculations performed tortuosity values do not provide a specific pattern for the three samples in three different path tracking directions. This indicates that the medium with porosity can have diverse and anisotropic complexities. Keywords: porous distribution, tortuosity, complexity of fluid flow, model of porous rock